Edukasi Senam Hamil sebagai Upaya Persiapan Persalinan yang Sehat dan Aman pada Ibu Hamil Trimester III - Ita Novianti; Asrianti Safitri Muchtar; Kiki Reski Rahmadani (Universitas Muhammadiyah Manado, 2026)
Limited knowledge of pregnancy exercise may reduce pregnant women's physical and psychological readiness for childbirth. This community service program aimed to improve the knowledge and practical skills of third-trimester pregnant women regarding pregnancy exercise as preparation for healthy and safe childbirth. The program applied a Participatory Action Approach through health education, demonstrations, supervised practice, interactive discussions, and evaluation using a one-group pretest-posttest design. Participants were third-trimester pregnant women from Ulo and Lanca Villages within the working area of Tellu Siattinge Community Health Center, Bone Regency, Indonesia. Knowledge and skills were assessed before and after the intervention to evaluate its effectiveness. The results showed a substantial improvement in participants' understanding of pregnancy exercise, with the proportion of women categorized as having good knowledge increasing from 21.4% before the intervention to 78.6% afterward. Furthermore, no participants remained in the poor knowledge category following the program. Participants also demonstrated improved practical skills in performing pregnancy exercise correctly under supervision. These findings indicate that integrating health education with demonstrations and hands-on practice is an effective strategy for enhancing pregnant women's knowledge and skills. This approach can strengthen maternal preparedness for childbirth and support efforts to promote healthy, safe, and positive pregnancy outcomes through community-based maternal health education programs.